Effects of prey deprivation on life table attributes of Neoseiulus idaeus Denmark and Muma (Acari: phytoseiidae) - Megevand, B.; Tanigoshi, L.K. (Elsevier, 1995)
Reproductive responses of Neoseiulus (= Amblyseius) idaeus Denmark and Muma ovipositing females were measured under three dietary regimes consisting of Mononychellus tanajoa (Bondar) or Oligonychus gossypii (Zacher) combined with specific periods (24, 48, 72, and 96 h) of starvation or periods of the same duration in which only cassava exudate was provided. These periods were applied after the females had laid at least one egg. The control treatments consisted of predators supplied with a continuous diet of either M. tanajoa or O. gossypii. Ovipositional period and survival were prolonged with prey deprivation. Following a period of prey deprivation, ovipositional rates recovered to the same or higher level than those of the control. Depending on the regime, females could withstand periods of 24 to 72 h prey deprivation without reducing their reproductive potential. Exudate feeding helped females to withstand periods of prey deprivation by sustaining their maintenance metabolism, and allowing a high reproductive potential to be maintained for extended periods. It was shown that oviposition was not chronological age-dependent but physiological age (measured as past egg production)-dependent and that, during periods of food shortage, resources were allocated primarily to maintenance at the expense of reproduction. Neither the sex ratio nor the hatching success of the progeny were affected by starvation.